FACTORS ASSOCIATED WITH GROWTH MONITORING AND PROMOTION AMONG CHILDREN 0-23 MONTHS IN MALONGO SUB-COUNTY, LWENGO DISTRICT, CENTRAL UGANDA. CROSS-SECTIONAL STUDY. - Naula , Ketty; Turumanya , Judah; Nalubega , Jane Frank (Student’s Journal of Health Research Africa, 2023)
BACKGROUND. The study explored factors associated with growth monitoring and promotion among children 0-23 months in Malongo sub-county, Lwengo district, central Uganda with specific objectives; assessment of Nutritional status of children, knowledge of caregivers, accessibility to Health facilities and Health-care package. METHODOLOGY. Qualitative and quantitative approaches were applied to draw clearer correlations of findings. Questionnaires with semi-structured open and closed ended questions were used to collect data. Health staff were interviewed and observations made with a simple checklist. Pre-tests were carried out for result consistency and validity prior to community subjection. RESULTS. Most caregivers were knowledgeable about GMP services. 200(75.5%) had easy access to health facilities. A number of children were wasted 67(25%), stunted 47(17.5%) and underweight 51(19.2%) as per Z-scores. 190(71.7%) female caregivers, 200(75.5%) were cohabiting/married. Education levels did not impact much on GMP , elites 85(32.1%) never practiced what they knew. 63(23.8%) households at times went without a meal due to poverty. 30(11.3%) caregivers received GMP counseling. 240(90.6%) found functional facilities but 115(43.4%) expressed varying challenges. Nutritional status of children was majorly affected by knowledge differences, unacceptable food regarded as medicine where restrictions deprived children of balanced diets. Poor health-seeking practices due to poverty and negative attitude about the health sector contributed to undefined malnutrition. CONCLUSION. Boy children were more affected than girls. Malnutrition taking both undernutrition and over nutrition was more pronounced in boys than girls. Thus, double malnutrition burden is equally on the rise in low- and middle-income countries thereby calling for more efforts in regular GMP to solve and prevent anomalies especially in the first a thousand days of life. RECOMMENDATION. Health service points should be equipped with knowledgeable personnel, functional screening tools and nutritional supplements. Positive attitude should be promoted in both caregivers and health workers. Policy makers should prioritize MCH services.